2020
DOI: 10.11591/ijece.v10i2.pp2045-2053
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of deep neural networks (DNN) with batch normalization for batik pattern recognition

Abstract: One of the most famous cultural heritages in Indonesia is batik. Batik is a specially made drawing cloth by writing Malam (wax) on the cloth, then processed in a certain way. The diversity of motifs both in Indonesia and the allied countries raises new research topics in the field of information technology, both for conservation, storage, publication and the creation of new batik motifs. In computer science research area, studies about Batik pattern have been done by researchers and some algorithms have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
0
12
0
3
Order By: Relevance
“…Nevertheless, a computer-aided design was not employed in this work to avoid overloading them with too many new things at once. Computer programs were previously proven successful in batik designs [17][18][19][20], but the local batik artisans were not keen to use them. The gradual incorporation of new techniques into traditional craftsmanship is an appropriate way to transform batik into modern fashion without losing its local identity and charm.…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a computer-aided design was not employed in this work to avoid overloading them with too many new things at once. Computer programs were previously proven successful in batik designs [17][18][19][20], but the local batik artisans were not keen to use them. The gradual incorporation of new techniques into traditional craftsmanship is an appropriate way to transform batik into modern fashion without losing its local identity and charm.…”
Section: -Discussionmentioning
confidence: 99%
“…Laitupa et al demonstrated the computer-based creation of new batik motifs [17], whereas Tian et al developed automatic batik flower patterns based on fractal geometry [18]. For pattern recognition, neural networks and deep learning have been implemented on batik fabrics [19,20]. To characterize fabric colors, smartphone colorimetry was demonstrated and compared with the standard CIE L*a*b* color measurement using a HunterLab spectrophotometer [21].…”
mentioning
confidence: 99%
“…Method Explicit Dropout [19] Weight degradation [22] DropConnect [20] Adjust the network size [23] Pooling stochastique [21] Batch normalization [24] (a) (b)…”
Section: Methods Empiricmentioning
confidence: 99%
“…Perform on small batch sizes dependent to reduce memory cost, normalization can rely for increase training accuracy [25]. The normalization layer minimize parameter change during propagated through the deep networks [26].…”
Section: Transformer Modelmentioning
confidence: 99%